Assisted hatching in cryopreservation protocols in patients with tuboperitoneal infertility - N. V. Protopopova; K. V. Krylova; E. B. Druzhinina; A. V. labygina; V. N. Dudakova (Acta Biomedica Scientifica, 2023)
At present, the problem of increasing the effectiveness of programs of assisted reproductive technologies and successful infertility treatment is still relevant. Assisted hatching used in the devitrificated embryo transfer facilitates the exit of the embryo from the pellucide zone. Yet the clinical efficacy of assisted hatching is relevant and debatable. There are no clear indications for the use of this technology, and no groups of patients have been identified.The aim of the study. To assess the effectiveness of laser hatching in the frozenthawed embryo transfer programs in patients with tuboperitoneal infertility.Materials and methods. We examined 300 women with tuboperitoneal infertility who had their embryos frozen for transfer. Inclusion criteria: age from 18 to 35 years; tuboperitoneal infertility; embryos cryopreserved for transfer. Exclusion criteria: age more than 36 years; other infertility factors. Women were divided into 2 groups: group 1 – women who had a frozen-thawed embryo transfer with preliminary laser hatching (n = 137); group 2 – control group (n = 163).Results. There were no differences between the groups in the mean age, body mass index and the age at menarche. According to the results of the embryological stage, there were also no differences in the number and quality of frozen embryos. The pregnancy rate in the group with preliminary laser hatching was 44.5 %, which is significantly higher than in the control group (42.3 %; р ≤ 0.001). We also found statistically significant differences in pregnancy outcomes: in the frequency of spontaneous miscarriages – 13.1 % and 20.2 % respectively (p ≤ 0.001), in the frequency of term deliveries – 30.7 % and 22.1 % respectively (p ≤ 0.001).Conclusion. In our study, the using laser hatching in women with tuboperitoneal infertility positively affected the embryos implantation in the cryopreservation protocols. Pregnancy and live birth rates are higher after using hatching technology, and the frequency of miscarriages up to 12 weeks is lower. This provide an opportunity to further study the effect of hatching on long-term outcomes, such as gestation course and childbirth.